Forma, função, produção: a publicidade da Unilabor e um projeto de modernidade - Silva, Osvaldo Bruno Meca Santos Da [UNIFESP] (2019)
The Unilabor was a small industrial plant that intended to bring together a modern design in the production of furniture and a community experience of work, inspired by the movement Economics and Humanism. It functioned in São Paulo from 1954 to 1967. An icon of the relationship between the Religious Community activity with Modern Art, the factory was the result of a partnership between the plastic artist Geraldo de Barros, head of the furniture design, and the Dominican friar João Baptista Pereira dos Santos, who led the proposal of humanization and "sharing of management" work in the company. The Unilabor used different strategies and visual materials in their advertising, which, besides the main purpose of the ads was selling furniture, also communicated to potential consumers like ideas, dedicated to a project of Modernity for the household. This research tried to understand how this publicity was made, once Unilabor was looking to become a company non-aligned with tools of capitalist system and, therefore, we evaluated how the advertising resources of the factory were used in practice, highlighting contradictions, and then explaining how the operative management, seen by the idealizer Friar João Batista, as a third way, in praxis, was spread in a diffuse way in publicity. Throughout the analysis, we also identified how the consumption relationship of these images was constituted, focusing the clients and/or the workers.